Health care ethics : lessons from intensive care - Melia, Kath M. (Ethics in Practice Ser., 2004)
This sociological study focuses on daily health care practice rather than on a specific ethical position. Applying the trans-philosophical principles put forth by Beauchamp and Childress (1994, 2001): respect for autonomy, non-maleficence, beneficence, and justice, Melia (U.